The Relevance of Ki Hajar Dewantara's "Being a Model" Philosophy for Christian Religious Teachers - Antoni Bastian (Jurnal Didaskalia, 2023)
The purpose of this study is to gain a deeper understanding of the duties and responsibilities of a Christian Religious Education teacher, who serves as the main actor in teaching. Ki Hajar Dewantara's philosophy on teacher education is considered to be a trusted and imitable example, which can be used as a basis for vocation. This research aims to examine how teachers can serve as role models and how this can be implemented by Christian Religious Education teachers in today's context. The study findings indicate that Christian teachers must lead by example in their teaching, fulfill their duties and calling as a gift in teaching, and make Jesus the main principle of their exemplary conduct. The purpose of this research is to illustrate the efforts made by Christian Religious Education teachers to enhance their duties and calling as teachers and to determine whether they have become role models in the present day.